Profile of an occupation – gardener - Schambeck, Arne [Verfasser] (My University, 2025)
"Climate change is leading young people increasingly to seek out occupational prospects in the green economy. Gardeners make an important contribution to the environment by growing fruit and vegetables, by laying out and caring for gardens and parks, and even by tending to graveyards. Gardening is an occupation which combines craft trade skills with specialist knowledge of plants, soils, nutrients and near-natural design. This profile sets out the tasks involved in the occupation’s seven specialisms and presents figures relating to training." (BIBB-Doku)
Keywords: S 6.1.1 Land-, Tier-, Forstwirtschaft und Gartenbau; 370; Gärtner; Berufsbild; Berufsbeschreibung